(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
The liquid–vapor phase equilibrium in the dimethyl sulfoxide–acetonitrile binary system was studied using a static method. The total saturated vapor pressure at the temperature range 293.15–323.15 K is measured. Partial pressures of dimethyl sulfoxide and acetonitrile were calculated by integrating the Gibbs–Duhem equation. Molar excess Gibbs energies were described by the Redlich–Kister equation, and correlation parameters were calculated. It was found that molar excess Gibbs energies are negative, and the deviation from ideality increases as temperature increases.